Hubungan Sanitasi Lingkungan Dengan Kejadian Diare pada Balita di Rantauparapat - Anggi Kurnia Adha Harahap; Lili Wardani Pohan; Nuraisah Tia Oktaviani Sitorus; Nurmaida Nurmaida; Tri Bayu Purnama (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
As of today, diarrheal diseases are still a worldwide problem, particularly in developing countries. The study aims to analyze factors that affect the incidence of diarrheal diarrhea in preinfant populations. This type of research is descriptive, using the design of a sectional parallel with the chi square test. The study was carried out in the prapate region by August 6, 2020. The population of the study was mothers-mothers who had toddlers living in praprons. The number of samples taken is 100 mothers with babies under the age of 5. Sample sorting is done with primary data obtained by giving questionnaires online. According to data analysis, toddlers who develop diarrhea, as many as 73% of toddlers develop diarrhoea, and as many as 51% of children develop diarrhoea, according to the mother, toddlers who poop more than 3 times a day as many as 39% of toddlers and toddlers who pass through soft liquid waste by 31% of children. P value 0.01 0.05, which means that the water source used has a meaningful relationship with child diarrhea in the prapate region, of 100 respondents to a large percentage of those who have bad clean water sources.